2004
DOI: 10.1016/j.jtcvs.2003.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial metabolic changes during pediatric cardiac surgery: A randomized study of 3 cardioplegic techniques

Abstract: For cyanotic patients (younger, with longer crossclamp times), cold blood cardioplegia with a hot shot is the best method of myocardial protection. For acyanotic patients (older, with shorter crossclamp times), cardioplegic technique is not critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…We have also shown that while for acyanotic patients the cardioplegic technique is not critical, for cyanotic patients, the use of cold blood cardioplegia with terminal warm blood cardioplegic reperfusion ("hot shot") improves the metabolic and functional recovery. The hot shot cardioplegia resulted in higher reperfusion ATP, ATP/ADP and glutamate levels than acyanotic patients, suggesting that this technique is advantageous only in stressed hearts [76]. Furthermore, the study shows that even if the blood cardioplegia is kept at cold temperature, this still offers a higher myocardial protection, compared to the crystalloid cardioplegia, confirming previous experimental and clinical results [77][78][79].…”
Section: Strategies Of Surgical Interventionsupporting
confidence: 83%
“…We have also shown that while for acyanotic patients the cardioplegic technique is not critical, for cyanotic patients, the use of cold blood cardioplegia with terminal warm blood cardioplegic reperfusion ("hot shot") improves the metabolic and functional recovery. The hot shot cardioplegia resulted in higher reperfusion ATP, ATP/ADP and glutamate levels than acyanotic patients, suggesting that this technique is advantageous only in stressed hearts [76]. Furthermore, the study shows that even if the blood cardioplegia is kept at cold temperature, this still offers a higher myocardial protection, compared to the crystalloid cardioplegia, confirming previous experimental and clinical results [77][78][79].…”
Section: Strategies Of Surgical Interventionsupporting
confidence: 83%
“…In adults, the superiority of blood over crystalloid cardioplegia was demonstrated experimentally [18], and was later demonstrated clinically in the pediatric population [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the warm protocol (CPB temperature 36.5 8C), oxygenated blood from the oxygenator was injected either in the aortic root or directly in the coronary ostia simultaneously with the cardioplegic solution (each vial of 10 ml is composed of magnesium chloride 1.6 g, potassium chloride 0.6 g, procaïne chloride 0.1 g, aqua ad 10 ml) given at a rate of 1-1.5Â the estimated physiologic coronary flow (5% of the cardiac output) for 1 min and repeated every 15 min [15]. The hematocrit was maintained at 25% in the cold protocol and 30% in the warm protocol and targeted to be at least 30% in both groups at discontinuation of CPB.…”
Section: Cpb Protocolmentioning
confidence: 99%
“…After the surgery, all patients were admitted to the pediatric intensive care unit (ICU) and were managed according to unit protocols (21,32).…”
Section: Methodsmentioning
confidence: 99%